2015
DOI: 10.3102/1076998614563393
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Imputation of Multilevel Missing Data—Rigor Versus Simplicity

Abstract: Multiple imputation is widely accepted as the method of choice to address itemnonresponse in surveys. However, research on imputation strategies for the hierarchical structures that are typically found in the data in educational contexts is still limited. While a multilevel imputation model should be preferred from a theoretical point of view if the analysis model of interest is also a multilevel model, many practitioners prefer a fixed effects imputation model with dummies for the clusters since these models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 27 publications
0
89
1
1
Order By: Relevance
“…We derive analytically why the variance of the random effects in the analysis model is positively biased when a cluster-specific fixedeffects imputation model, instead of a multilevel imputation model, is used. Further, we find that beyond the three factors governing this bias that were already identified in Drechsler (2015) (for the special case of random intercept models), the bias also depends on the mean and variance of the observed data (which are governed by the missing data mechanism). We present support for these findings using simulation studies and a real data application.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…We derive analytically why the variance of the random effects in the analysis model is positively biased when a cluster-specific fixedeffects imputation model, instead of a multilevel imputation model, is used. Further, we find that beyond the three factors governing this bias that were already identified in Drechsler (2015) (for the special case of random intercept models), the bias also depends on the mean and variance of the observed data (which are governed by the missing data mechanism). We present support for these findings using simulation studies and a real data application.…”
Section: Introductionmentioning
confidence: 97%
“…To our knowledge, the impact on random effects if fixedeffects models with cluster-specific slopes are used for imputation has not yet been studied analytically, despite the demand for such research (Drechsler, 2015;Lüdtke et al, 2017;Grund et al, 2016). Our paper closes this research gap by comparing cluster-specific fixed-effects imputation and multilevel imputation and generalizing the evaluations to all types of random coefficient models.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…If participants do not have transportation, bus passes will be mailed to the participants' desired location so that they can attend follow-up visits (many local shelters offer onsite mailboxes). Should high rates of missing data occur, we will employ multiple imputation methods designed for longitudinal data, [85] such as R packages mice [86] and pan. [87] Other studies comparing usual care to a smart phone intervention have observed equal rates of attrition across study arms.…”
Section: Potential Problems and Alternate Strategiesmentioning
confidence: 99%